2020
DOI: 10.1111/puar.13158
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Reputation Barometer for Public Agencies: A Validated Instrument

Abstract: Reputation is of growing interest for the study of public bureaucracies, but a measurement that can discern between the subdimensions of reputation and is validated on real-life audiences has remained elusive. The authors deductively build, test, and cross-validate a survey instrument through two surveys of 2,100 key stakeholders of the European Chemicals Agency, the European Union chemicals regulator. This empirical tool measures an agency's reputation and its building blocks. This scale represents an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…This finding is significant as audiences are the core of reputation, and for public organizations it is crucial to select and gauge the perceptions of their most relevant ones over time (Christensen and Gornitzka 2019; Maor 2020). In this regard, the Overman, Busuioc, and Wood's (2020) study is outstanding—they measured 13 internal and external audiences of the European Chemicals Agency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is significant as audiences are the core of reputation, and for public organizations it is crucial to select and gauge the perceptions of their most relevant ones over time (Christensen and Gornitzka 2019; Maor 2020). In this regard, the Overman, Busuioc, and Wood's (2020) study is outstanding—they measured 13 internal and external audiences of the European Chemicals Agency.…”
Section: Resultsmentioning
confidence: 99%
“…In the second group, content analysis of the media coverage (e.g., Maor and Sulitzeanu‐Kenan 2013, 2016), interviews with different audiences (e.g., Groenleer 2014), surveys (e.g., Capelos et al 2016), or standardized instruments designed to measure reputation in public administration specifically (e.g., Lee and Van Ryzin 2019; Overman, Busuioc, and Wood 2020) were used for this purpose.…”
Section: Characteristics Of the Samplementioning
confidence: 99%
See 1 more Smart Citation
“…It is vital for public employers to be visible and distinct in their employer branding, as potential recruits are often simply unaware of potential employers (Baum and Kabst 2014). Employer branding measures should also be compared across channels (Fay and Zavattaro 2016), and the way in which they interact with public employers’ reputation (Overman, Busuioc, and Wood 2020) should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that bureaucrats experience competing reputational concerns (sector, agency, ministry, cabinet), and that the focus of reputational concerns varies according to seniority and task environment (Kolltveit et al, 2019). Moreover, "reputation" is not monolithic, but encompasses a range of technical, procedural, moral, and performative forms (Carpenter, 2010;Overman et al, 2020). Building on these insights, it is anticipated that under conditions of populist pressure, manifest through anti-elite rhetoric, bureaucrats will become highly concerned with their procedural or technical reputation as they seek to defend their legitimacy as impartial administrators and experts.…”
Section: Stage 2: a Change Of Attitude-emotionalized Blame Attribution Challenges Perceptions Of Accountability (Perceptions Of Accountabmentioning
confidence: 99%